Making Space for Visual Literacy in Literacy Teacher Preparation: Preservice Teachers Coding to Design Digital Books - Eutsler, Lauren (TechTrends, 2021)
To reduce the lag between highly visual texts in elementary classrooms and a lack of emphasis on visual literacy in teacher preparation, this study explored preservice teachers’ coding in the design of a visually-enhanced digital book. A qualitative case study shaped the research design and data collection, including ten digital book artifacts and reflections from preservice teachers. Content analysis identified modes of communication evident within digital books, while thematic analysis examined reflections. One book included all modes of communication. Books lacked consistency of supportive, accessible, and engaging features such as narration, captions, and scene detail. Reflections indicated possibilities and visual affordances of digital book reading in the classroom, at the cost of technological challenges and time required to use a new tool. Findings call for a shift to acknowledge and incorporate visual literacy theories and practices into teacher preparation programs to prepare preservice teachers for digitally literate classrooms.